Persepsi Konsumen Terhadap Bauran Promosi (Promotional mix) pada Matahari Department Store Bengkulu - seprianti eka putri (Unib Press Universitas Bengkulu, 2014)
The objective of this research is to know the consumers’ perception toward promotional mix at Matahari Departement Store Bengkulu. This research represents of survey which representing problem in the form of fact in this time from a certain phenomenon. The data was used primary data through distribution of questionnaire. The respondents in this research are consumers’ of Matahari Departement Store equal to 100 respondents. The sample taken was accidental sampling. The data analysis was used descriptive with frequency distribution, means, and percentages. Pursuant to result of data analysis obtained result of that the consumers’ perception toward promotional mix at Matahari Departement Store have an a good level.